Coach-guided instructional cues and pre-service teachers’ netball shooting skill acquisition in physical exercise and sports context - Donkor, Samuel Kofi; Adenyoh, Courage Kobla; Osei, Charity Atteh; Nkrumah, Abena Adasa; Atsu, Selase Fortune; Appiah, Michael; Agortey, Julius Jerry; Darko, Regina Akuffo; Asare, Mavis; Okala, Chikaike (Faculty of Natural and Applied Sciences Journal of Mathematics, and Science Education, 2023)
Understanding the differential effect of the instructional cue (IC) of the coach can provide valuable insight into how instructional guidance impacts learning outcomes. Both coach-guided learning and self-directed learning are instructional strategies that can potentially maximize or minimize achievement in an instructional setting. Therefore, the purpose of the study was to use two instructional schedules to examine the influence of coach-guided IC on pre-service teachers' acquisition of netball shooting skills in sports and exercise practical settings. Using descriptive procedures, a digital video was utilized to record classroom events of pre-service teachers (n=77) and professional sports and exercise instructors (n=4). The video-recorded session lasted 1 hour (60 minutes). An event recording instrument was designed and used to document the frequency of shooting events during the instructional schedule. Two experienced independent recorders used the event recording instrument to note down shooting events in the two instructional schedules. Inter-observer agreement procedures were used to assess the reliability of data collected for the study. The data collection instruments were deemed valid by experienced researchers who ascertained the credibility of using these tools for collecting precise data. Graphical analyses were conducted to determine the influence of coach-guided IC on pre-service teachers' acquisition of netball shooting skills in sports and exercise practical settings. Findings confirmed the superiority of the instructional schedule that incorporated coach-guided IC over the instructional schedule carried out without coach-guided IC. Therefore, we concluded that coach-guided ICs yielded a stronger influence on the learning process than self-guided learning.